1999
DOI: 10.1002/(sici)1097-4644(19990501)73:2<164::aid-jcb3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Notch-1 inhibits apoptosis in murine erythroleukemia cells and is necessary for differentiation induced by hybrid polar compounds

Abstract: Strikingly increased expression of notch-1 has been demonstrated in several human malignancies and pre-neoplastic lesions. However, the functional consequences of notch-1 overexpression in transformed cells remain unclear. We investigated whether endogenously expressed notch-1 controls cell fate determination in mouse erythroleukemia (MEL) cells during pharmacologically induced differentiation. We found that notch-1 expression is modulated during MEL cell differentiation. Premature downregulation of notch-1 du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
1
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 39 publications
5
89
1
2
Order By: Relevance
“…15,18,19,24 For this reason, we aimed to characterize the physiological role of the Notch pathway in erythropoiesis by comparing WT and RBPjk À/À embryos. Despite the absence of intraembryonic hematopoiesis in the RBPjk À/À embryos and the presence of different angiogenic abnormalities in the yolk sac, we found that primitive hematopoiesis does occur in the yolk sac of the RBPjk À/À embryos (Figure 1a), similar to the Notch1 À/À mutants.…”
Section: Absence Of Notch Signaling Results In Increased Number Of Ermentioning
confidence: 99%
See 2 more Smart Citations
“…15,18,19,24 For this reason, we aimed to characterize the physiological role of the Notch pathway in erythropoiesis by comparing WT and RBPjk À/À embryos. Despite the absence of intraembryonic hematopoiesis in the RBPjk À/À embryos and the presence of different angiogenic abnormalities in the yolk sac, we found that primitive hematopoiesis does occur in the yolk sac of the RBPjk À/À embryos (Figure 1a), similar to the Notch1 À/À mutants.…”
Section: Absence Of Notch Signaling Results In Increased Number Of Ermentioning
confidence: 99%
“…Although previous reports have attempted to decipher which is the Notch function in apoptosis of erythroid cells, 15,19 this is the first time that this question is addressed in primary cells. The use of cell lines in the previous published reports may explain the controversial data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, hybrid polar compounds have been used to induce differentiation in many different tissues of all embryonic lineages [2]. HMBA is a prototype compound from this class, and has been shown specifically to differentiate the MEL murine erythroleukemia cell line [2,3], with concomitant downregulation of Notch1 [4].Notch1 is a transmembrane receptor important in stem cell renewal and T versus B lineage differentiation, which has a unique mechanism of activation, releasing an intracellular subunit upon ligand binding, which translocates into the nucleus to induce the expression of target genes such as Deltx, Hes1 and pTalpha [5]. Mutations in its HD and PEST domains have recently been strongly implicated in the pathogenesis of T-ALL, being found in more than half of these patients [6].…”
mentioning
confidence: 99%
“…In general, hybrid polar compounds have been used to induce differentiation in many different tissues of all embryonic lineages [2]. HMBA is a prototype compound from this class, and has been shown specifically to differentiate the MEL murine erythroleukemia cell line [2,3], with concomitant downregulation of Notch1 [4].…”
mentioning
confidence: 99%